2020
DOI: 10.1055/s-0039-1700958
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fat Grafting in Cosmetic Breast Surgery

Abstract: The role of fat grafting to the breasts has evolved in the recent past, gaining several new applications within both reconstructive and aesthetic surgery. Initially used for reconstructive purposes to fill lumpectomy defects or to correct residual contour deformities after breast reconstruction, it has since made its way into cosmetic breast surgery and has grown to encompass a wide variety of new indications. Fat grafting in aesthetic breast surgery may be performed as a form of primary autologous breast augm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…During the last few years, SVF-based autologous cellular therapies have been tested in several clinical settings, like scars [ 2 , 7 ], hemifacial atrophy [ 8 ], breast reconstruction [ 9 ], wound healing and cancer therapy [ 10 ], hair regrowth [ 11 ], breast augmentation [ 12 ], and in vitro applications [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, SVF-based autologous cellular therapies have been tested in several clinical settings, like scars [ 2 , 7 ], hemifacial atrophy [ 8 ], breast reconstruction [ 9 ], wound healing and cancer therapy [ 10 ], hair regrowth [ 11 ], breast augmentation [ 12 ], and in vitro applications [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 to 3 mL of fat injection is required to achieve the aesthetic goal. 12,13 The space for fat injection is considerably smaller in the lower eyelid, and because of its thin and less elastic skin texture, the injected fat space may be more restricted. The fat graft in lower eyelid can be distributed equally as a thinner layer with theologically better nutrition supplement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that resistance to platinum-based chemotherapy may be due to somatic reversion mutations or intragenic deletions that restore BRCA1 or BRCA2 function in breast cancer [32]. Cytochromes P450s (CYPs) are composed of a superfamily which catalyze the metabolism of drugs and other substances.…”
Section: Discussionmentioning
confidence: 99%